PERENCANAAN STRATEGIS TEKNOLOGI INFORMASI: Studi Kasus Pada Perguruan Tinggi Lepisi Tangerang - Ahmad Yani; M.Sukrisno Mardiyanto (PETIR, 2019)
Strategic plan IS/IT is an identification process portofolio application IS bases on computer that will support organization in execution of business plan and implement its business target. Strategy Planning IS/IT studies influence IS/IT to business performance and contribution for organization in selecting strategic steps. In other hand strategic plan IS/IT also explains various of toolses, technique and framework for manjemen to harmonize strategy IS/IT with business strategy, even prowl just pass by innovative technology implementation. In course of strategic plan IS/IT with object of LEPISI College research this, writer uses framework according to Jhon Ward and Peppard. Concept of idea from strategic plan IS/IT from Jhon Ward left from existence of invesment condition IS and TI in the past that less can give benefit for target of organization business, catch business opportunity, and existence of phenomenon growing of competitive excellence organization because can exploit potency IS and IT. Situation is referred can happen because strategic plan IS and TI that out of focus at business, conducted by part that less understand business opportunity, and make only strategy because technology need. The result of research this is the have the shape of proposal of strategy planning framework Information system that can be used at college LEPISI. Keyword: Information system Strategic plan/Information Technology, Methodologies IS/IT